Implementation of mindfulness-acceptance-commitment protocol for injured athletes : an action research study - Jumroonrojana, Karn (2017)
Mindfulness-Acceptance-Commitment (MAC) protocol has been implemented and studied for the purpose of performance enhancement with several positive results in the past 10 years. More recently, an increasing, but limited, number of MAC studies have also been done in the field of sport injury prevention and rehabilitation. Since MAC is a protocol with flexible implementation, sport psychology consultants, especially novice, can be confused by a wide range of its strategies. It is important to study implementation because it doesn’t provide only information about the effect but also detailed contents and mechanisms of an intervention, which will reduce variability and fidelity of it. The purpose of this action research case study was to describe and evaluate implementation of the MAC protocol with injured athletes in a small group setting by a novice consultant. 4 injured athletes were included in a 6-session educational MAC program which was conducted in a period of 4 weeks. Data was collected by reviewing participants’ assignments, semi-structured interviews, feedback questionnaires, and reviewing the consultant’s reflective diary. Narrative and content analyses were used in the study. The results suggest that novice consultants who want to use the MAC protocol to work with a group of injured athletes should emphasize the importance of adequate case formulation, time management, creativity in facilitating strategies, experience of the approach and adaptation of the protocol to sport injury. Also, mindful movement technic was an effective tool. This study provides detailed description and evaluation of the program for consultants and future researchers to further develop mindfulness- and acceptance-based interventions for sport rehabilitation.